Multiple Intelligence: Learning with Interactive eGuide Book for Enhancing Young Children’s Intrapersonal and Interpersonal Intelligences - Rasul, Shareen Gulam; Por, Fei Ping; Kanesin, Thoolasi (Universitas Muhammadiyah Purwokerto, 2023)
Young children aged 4 to 6 years old experience greater impact on their emotional and social development compared to adults during the lockdown period. The prolong absence from school confines their exposure to engage outdoor activities and learning activities with peers. Consequently, they tend to be clingier to their parents. Therefore, this study aims to develop intrapersonal and interpersonal intelligences among young children through the interactive eGuide book created in this study. The interactive eGuide book contains professionally selected learning activities which were carried out for four weeks with the facilitation of parents. The samples involved a total of 12 parents residing in Selangor, Malaysia who had given consent to participate in this study. The young children’s reactions related to intrapersonal and interpersonal intelligences were observed and recorded. Semi-structured interviews were conducted to explore the children’s development before and after utilising the interactive eGuide book. Thematic analysis was done to identify themes and subthemes. The findings were positive as there was a great intrapersonal and interpersonal improvement among the young children. They were able to regulate their emotions and build self-confidence; they were more expressive to communicate their feelings with others and demonstrated decision-making skills. The interactive eGuide book is proposed to also be used in normal situations especially by first-time parents and preschool teachers to develop children’s intrapersonal and interpersonal intelligences so that they are able to analyse their strengths and weaknesses, work collaboratively and create worthwhile relationships since young.